Construction of MXene/MOFs nano-coatings on PU sponge with enhanced interfacial interaction and fire resistance towards efficient removal of liquid hazardous chemicals. (1st June 2023) - Deng, Guojun; Sun, Mengnan; Shi, Yongqian; Feng, Yuezhan; Lv, Yuancai; Tang, Longcheng; Gao, Jiefeng; Song, Pingan
Abstract: The leaked hazardous chemicals pose significant risks due to their harmful and combustible nature. Removing them from the environment has become an arduous task for both the industrial sector and academic community. In this paper, Ti3 C2 Tx (MXene) nanosheets and metal-organic framework (ZIF-8 MOFs) functionalized polyurethane (PU) sponges (PU-Ti3 C2 Tx -MOF sponges) were prepared by immersion coating and in-situ growth techniques. The as-prepared PU-Ti3 C2 Tx -MOF sponge exhibited superior hydrophobicity with a water contact angle of 135°. Additionally, it demonstrated a higher adsorption capacity and rapid adsorption ability for liquid hazardous chemicals within 1 min, while still maintaining good reusability for adsorption. The PU-Ti3 C2 Tx -MOF2 sponge had the highest adsorption capacity of 48–91 times of its own mass for liquid hazardous chemicals. Furthermore, it demonstrated excellent reusability, maintaining its high adsorption capacity for oils and organic solvents even after being used 5 times. These results surpass previously reported data and highlight the superior capabilities of the PU-Ti3 C2 Tx -MOF2 sponge. Meanwhile, the PU-Ti3 C2 Tx -MOF sponge maintained the excellent flame retardancy and compressibility. This work provides a new pathway for the design of functional polymer sponges and their potential application in rapid elimination of the leaked hazardous chemicals. Graphical abstract: Image 1 Highlights: Functionalized sponges were prepared by coating and in-situ growth methods. Lightweight functional sponges showed superior hazardous chemicals removal. Lightweight functional sponges outperform previous reported absorbents. Lightweight functional sponges exhibited high fire safety.